2015
DOI: 10.1089/bfm.2014.0059
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk and Breastfeeding Outcomes in Infants with Congenital Heart Disease

Abstract: Mothers who have infants diagnosed with congenital heart disease should be encouraged to initiate pumping for their infants. Future research is warranted regarding the dose response of HM and specific health outcomes and the need for postdischarge services for these families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 12 publications
1
44
0
2
Order By: Relevance
“…59 For neonates and infants, particularly in low-and middle-income countries, human breast milk is the preferred form of enteral feeding, although the practicalities of maintaining breast milk production in this context may be challenging. 61 Breast milk is cost-effective, has immunological benefits, promotes better absorption of trace elements, and may even lower the risk of developing necrotising enterocolitis when used exclusively. 62 In the setting where tight fluid restriction is required, it may be necessary to increase the energy density of feedsboth for formula and expressed breast milk.…”
Section: Postoperative Nutritionmentioning
confidence: 99%
“…59 For neonates and infants, particularly in low-and middle-income countries, human breast milk is the preferred form of enteral feeding, although the practicalities of maintaining breast milk production in this context may be challenging. 61 Breast milk is cost-effective, has immunological benefits, promotes better absorption of trace elements, and may even lower the risk of developing necrotising enterocolitis when used exclusively. 62 In the setting where tight fluid restriction is required, it may be necessary to increase the energy density of feedsboth for formula and expressed breast milk.…”
Section: Postoperative Nutritionmentioning
confidence: 99%
“…That being said, it is still possible to improve breastfeeding outcomes in newborns with congenital anomalies so long as the primary care team adopts the necessary measures [30]. Torowicz et al’s prospective cohort study of 62 mothers has shown that the attitudes of the institution and the advocacy for breastfeeding are key for the initiation and maintenance of breastfeeding in mothers who have infants with complex congenital heart diseases [31]. …”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the proportion of infants with CHD who were predominantly breastfed or receiving any breastmilk during the first year of life would be comparable to the general population, as it has been shown mothers can successfully breastfeed their infant with CHD with proper support and education. 33,42 Specific Aim 2: Describe growth outcomes among infants with CHD during the first year of life, and the relationship between feeding practices and growth. We hypothesized that there would be better growth outcomes (weight-for-age, length-forage, head circumference-for-age, and weight-for-length Z-scores) in the infants that were predominantly breastfed or fed any breast milk compared to those that were predominantly formula fed, as it has been shown before that bottle-fed infants fell further from their growth curves than breastfed infants did.…”
Section: Chapter 3 Aimsmentioning
confidence: 99%